Complications and outcome of cats with congenital extrahepatic portosystemic shunts treated with thin film: Thirty‐four cases (2008‐2017). (19th November 2019) - Valiente, Paula; Trehy, Mary; White, Rob; Nelissen, Pieter; Demetriou, Jackie; Stanzani, Giacomo; de la Puerta, Benito
Abstract: Background: Congenital extrahepatic portosystemic shunts (CEHPSS) are rare in cats. Outcome after attenuation of CEHPSS with thin film has been described in a small number of cases. Objectives: To describe the clinical presentation, postoperative complications, and outcome of cats treated with thin film to attenuate CEHPSS. Animals: Thirty‐four cats with CEHPSS were identified from the database of 3 institutions over 9 years. Methods: Retrospective study. Medical records were reviewed to identify cats with a diagnosis of a CEHPSS that underwent surgical attenuation. Congenital extrahepatic portosystemic shunts were suspected from clinical signs, clinicopathologic findings, and diagnostic imaging, and confirmed at exploratory laparotomy. Cats treated with thin film band attenuation were included. Postoperative complications and follow‐up were recorded. Results: Complications were recorded in 11 of 34 cats. Deaths related to CEHPSS occurred in 6 of 34; 4 cats did not survive to discharge. Persistent seizures were the cause of death in 4 cats. Seizures were recorded in 8 of 34 cats after surgery; all these cats received preoperative antiepileptic drugs. Serum bile acid concentrations normalized in 25 of 28 of the cats for which data was available. Three cats had persistently increased serum bile acid concentrations and underwent a second exploratory laparotomy. One had a patent shunt, the other 2 had multiple acquired portosystemic shunts. Median follow‐up was 8 months (0.5‐84 months). Conclusions and Clinical Importance: Congenital extrahepatic portosystemic shunts attenuation using thin film in cats carries a good short‐ and mid‐term prognosis if they survive the postoperative period. Seizures were the most common cause of death.